Penafsiran Tentang Jilbab Dalam Al-Qur’an Surah Al-Ahzab [33] Ayat 59 Menurut Buya Hamka Pada Tafsir Al-Azhar - Sugiarto, Fitrah; Nurwathani Janhari, M.; Hotimah, Husnul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
The Qur’an is the holy book of Muslims, in which there are many rules of Allah, one of which is the rules are many of Allah, one of which is the rules of regarding the ethics of Muslim women wearing the hijab. From the analysis of language, it can be concluded that the hijab is a wide, loose garment that covers the whole body. Meanwhile, the interpreters differ on the meaing of “Let them extend their headscarves all over the body.” Among their interpretations of the verse is covering his face and head, and showing only his left eye, covering the whole body and half of the face by showing both eyes, and stretching the cloth to cover the head to the chest. So, we can conclude that from the beginning the mufassirs agreed on the obligation of the hijab and differed in opinion about the meaning of lengthening the hijab. In the paper, we use a qualitative descriptive method, namely by utilizing qualitative data and describing it descriptively by analyzing events, phenomena, events, social activities, perceptions and thoughts of people both individually and in groups. Then as for the results of our research, namely the hijab wide, loose, and covers the whole body.